2010
DOI: 10.1038/npp.2010.75
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 Receptor Immunoreactivity in the Prefrontal Cortex: Comparison of Schizophrenia and Major Depressive Disorder

Abstract: We recently demonstrated that measures of CB1R mRNA and protein were significantly reduced in DLPFC area 9 in schizophrenia subjects relative to matched normal comparison subjects. However, other studies have reported unaltered or higher measures of CB1R levels in schizophrenia. To determine whether these discrepancies reflect differences across brain regions or across subject groups (e.g., presence of depression, cannabis exposure, etc), we used immunocytochemical techniques to determine whether lower levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 88 publications
(127 reference statements)
7
66
2
Order By: Relevance
“…In the current study, however, we observed no effect of cannabis exposure on CB 1 R density or mRNA in the DLPFC, in agreement with other studies in the DLPFC (Dean et al, 2001;Eggan et al, 2010) and superior temporal gyrus (Deng et al, 2007).…”
Section: Effects Of Continuous and Non-continuous Variablessupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, however, we observed no effect of cannabis exposure on CB 1 R density or mRNA in the DLPFC, in agreement with other studies in the DLPFC (Dean et al, 2001;Eggan et al, 2010) and superior temporal gyrus (Deng et al, 2007).…”
Section: Effects Of Continuous and Non-continuous Variablessupporting
confidence: 81%
“…In contrast to the receptor binding studies, reduced cortical CB 1 R mRNA and protein expression have been found in the post-mortem DLPFC (Brodmann's areas 9 and 46) in SCZ (Eggan et al, 2008;Eggan et al, 2010), whereas another study (Koethe et al, 2007) found no change in the density of CB 1 R immunopositive cells in the anterior cingulate cortex in SCZ. Importantly, a recent imaging study using the novel positron emission tomography (PET) CB 1 R tracer […”
Section: Introductionmentioning
confidence: 69%
“…Neuroanatomical and positron emission tomography studies have demonstrated that CB 1 receptor mRNA and protein occur in most layers of the human neocortex (Westlake et al, 1994;Lopez de Jesus et al, 2006;van Laere et al, 2008;Eggan et al, 2010). We studied synaptic transmission using patch-clamp electrophysiological methods in cortical tissue removed during neurosurgery to eliminate epileptogenic foci.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in women diagnosed with depression, serum content of AEA and 2-AG was decreased, suggesting that hypoactivity of the EC system may also be present in patients (Hill et al 2009). Unfortunately, data regarding CB1r density in the frontal cortex of patients with major depression appear to be inconsistent: there have been reports of decreased CB1 density (Koethe et al 2007), no alterations (Eggan et al 2010), or even upregulation (Hungund et al 2004;Vinod et al 2010;Choi et al 2012). Possible reasons for this complexity include ante-and postmortem factors such as medication, substance use, brain pH, and different methodological approaches for evaluating receptor levels.…”
Section: Depressionmentioning
confidence: 92%